Spatial Analysis of Residential Fragmentation and Its Impact on Infrastructure Services (A Case Study of Al-Dour City) - Dr. Fatima Ibrahim Taama (Journal of College of Education, 2025)
The study is unique to the city of Ad-Dur in the urban aspect for the year 2023 AD, which has an area of (1586) hectares and includes 13 neighborhoods, and a population of (25935) people. The phenomenon of residential fragmentation is one of the urban phenomena that has emerged recently in the city of Ad-Dur as a result of many reasons, the most prominent of which is the housing crisis problem. This phenomenon has become a challenge to the residential structure, and the study came to shed light on this phenomenon and analyze the factors and causes leading to it and its impact on the efficiency of infrastructure services. The researcher adopted the field survey method and the use of government data and The descriptive analytical approach was adopted, adopting a quantitative approach. A random sample of (10%) of the total housing units resulting from the split was taken through a questionnaire. The study concluded that the Muhammad Al-Dari neighborhood led the way with (250) split housing units, while the Al-Zahour neighborhood came in last with (20) split housing units. It was found that there were deficiencies in the efficiency of infrastructure services due to the split housing situation. Recommendations were made, including supporting and encouraging housing companies to build residential complexes at competitive prices to reduce the phenomenon of housing split